2015
DOI: 10.1149/2.0721514jes
|View full text |Cite
|
Sign up to set email alerts
|

Aging Analysis of Graphite/LiNi1/3Mn1/3Co1/3O2Cells Using XRD, PGAA, and AC Impedance

Abstract: The performance degradation of graphite/LiNi 1/3 Mn 1/3 Co 1/3 O 2 (NMC) lithium ion cells, charged and discharged up to 300 cycles at different operating conditions of temperature and upper cutoff potential (4.2V/25 • C, 4.2V/60 • C, 4.6V/25 • C) was investigated. A combination of electrochemical methods with X-ray diffraction (XRD) both in situ and ex situ as well as neutron induced PromptGamma-Activation-Analysis (PGAA) allowed us to elucidate the main failure mechanisms of the investigated lithium ion cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
263
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 236 publications
(281 citation statements)
references
References 62 publications
17
263
1
Order By: Relevance
“…In other words, a high irreversible capacity during the first charge does not necessarily mean that a high amount of lithium is lost irreversibly, but rather that after the HE-NMC activation not all of the extracted lithium can be reinserted into the cathode active material (even though for mechanistically different reasons, an irreversible capacity loss is also observed for NCM 111). 41,42 However, for all compositions an offset between capacity loss during the first cycle and the cyclable lithium capacity in the graphite anodes of about 20 -27 mAh/g is observed. This capacity offset must correspond to an irreversible loss of active lithium in side-reactions during the first charge/discharge cycle and cannot be assigned to typical anode SEI losses, as the SEI was already preformed on the graphite electrodes.…”
Section: Resultsmentioning
confidence: 91%
“…In other words, a high irreversible capacity during the first charge does not necessarily mean that a high amount of lithium is lost irreversibly, but rather that after the HE-NMC activation not all of the extracted lithium can be reinserted into the cathode active material (even though for mechanistically different reasons, an irreversible capacity loss is also observed for NCM 111). 41,42 However, for all compositions an offset between capacity loss during the first cycle and the cyclable lithium capacity in the graphite anodes of about 20 -27 mAh/g is observed. This capacity offset must correspond to an irreversible loss of active lithium in side-reactions during the first charge/discharge cycle and cannot be assigned to typical anode SEI losses, as the SEI was already preformed on the graphite electrodes.…”
Section: Resultsmentioning
confidence: 91%
“…9,11,13 While the error bars are hardly visibly for cutoff voltages ≤4.4 V and at low cycle numbers at a cutoff of 4.6 V, the error bars at higher cycle numbers significantly increase, which is due to the delayed onset of the so-called rollover-failure for the two cells. This failure mechanism was described previously by Dubarry et al and Burns et al and was shown to be due to growing kinetic resistances or more generally an impedance buildup.…”
Section: Resultsmentioning
confidence: 99%
“…[66][67][68] Including those effects will be part of future investigations, as they are not crucial for the general improvement of the introduced SEI model representation by two conductivities.…”
Section: 62mentioning
confidence: 99%